MENILIK GAYA KEPEMIMPINAN OTORITER - Yudha Aditya; Leonard Adrie Manafe; Fajar Tinovita Sari (JURNAL ILMIAH EDUNOMIKA, 2023)
The purpose of this study was to analyze the application of authoritarian leadership style at PT. Kurnia Nata Kencana. The research method uses a qualitative approach with informants are five people who come from several division. Collection of information through interviews and literature study. The result shows that the head of division is included in the category of authoritarian leaders, supported by the following characteristics: First, the leader bears the burden of the organization and carry out supervision, control over his own decisions; Second, authoritarian leaders don’t provide opportunities for conveying ideas; Third, authoritarian leaders have work discipline and focus on the result; Fourth, leaders make their own policies without the interference of others; Fifth, authoritarian leaders have low trust in their employees; Sixth, authoritarian leaders use one-way communication; Seventh, leaders are task oriented and pay little attention to employee welfare; Eight, authoritarian leaders use power to give orders, rules, and prohibitions; Ninth, authoritarian leaders act in a dictatorial manner.